How do plants read their own shapes?. Issue 2 (17th August 2016) - Hamant, Olivier; Moulia, Bruno
Summary: Although the sensing of shape and deformation was historically involved in the control of animal locomotion, it is now increasingly being incorporated in developmental biology. Proprioception, the perception of the self, is particularly key to the question of the reproducibility of shapes: the many regulators of growth may lead to a large array of geometries, but shape sensing restricts these diverse outputs to a limited number of forms. Mechanistically, and in addition to geometrical feedback onto the diffusion and transport of molecular factors, we highlight the role of shape‐derived mechanical stress and strain in this process. Through examples at the cell, tissue and organism scales, it appears that such mechanical feedback adds robustness to morphogenesis. Interestingly, synergies exist between shape sensing and response to external cues, such as wind and gravity. Understanding the molecular basis of proprioception is now within reach and opens up many avenues for an integrative view of development. Contents Summary 333 I. Introduction: a brief history of proprioception 333 II. The possible mechanisms behind shape sensing 334 III. Evidence for a role of mechanical cues in proprioception 334 IV. Conclusion: proprioception and the control of growth and form 336 Acknowledgements 336 References 337